PENERAPAN AUGMENTED REALITY UNTUK MEDIA PEMBELAJARAN ALAT MUSIK GAMELAN SUNDA BERBASIS ANDROID DENGAN METODE MARKER BASED TRACKING - Ardi Rudini, (2024)
Sundanese Gamelan is one of the traditional musical instruments of Indonesia originating from West Java. Sundanese Gamelan is used for various events such as celebrations, ceremonies, and entertainment. In dance, Sundanese Gamelan plays an important role in expressing emotions and nuances in the dance. In ceremonies, Sundanese Gamelan plays an important role in creating a conducive and sacred atmosphere. Some examples of events that use Sundanese Gamelan are traditional wedding ceremonies, Degung, and art performances. However, currently, traditional musical instruments are difficult to find or showcase, and many people are not familiar with their own regional musical instruments. Lack of interest and curiosity towards traditional arts, especially Gamelan, becomes the main factor in the decline of traditional culture because people spend more time using gadgets or smartphones to access social media or play games. To address this issue, an application is needed to educate users to learn Sundanese Gamelan musical instrument easily accessible by users through gadgets or smartphones by displaying 3D visual Gamelan that is similar to the original Gamelan. Therefore, this study proposes a Sundanese Gamelan musical instrument learning media application by implementing Augmented Reality technology and using the Marker-Based Tracking method. Keyword: Gamelan,Augmented Reality, Aplikasi Edukasi, 3D, Marker Based.